PERANCANGAN SISTEM INFORMASI CARA MENGGALI POTENSI DIRI DENGAN MENGGUNAKAN METODE MBTI (MYERS-BRIGGS TYPE INDICATOR) - Dwi Budi Srisulistiowati (JURNAL MITRA MANAJEMEN, 2014)
ABSTRACTION In the era of intense competition as now, when the capacity of work is very limited, thousandsof people competing to get jobs in various companies. Various attempts were made tocandidates reaching hopes. But, in fact, most of us are often stuck in the mindset that we mustwork in a particular field, habits to be more interested in the kinds of jobs that are consideredestablished by most people, and old ways of linking education background should be inaccordance with job. This habit certainly hinder the process of our own progress, so greatexpectations often are not accompanied by proper effort. Each company should use this MBTI test instruments in the process of selecting the candidateof their employees, so that job satisfaction can be achieved due to individual personality typescan optimize the work environment. Individuals who work in accordance with the type ofpersonality is predicted to be more satisfied and have a greater chance of success in theirwork than those who work not in accordance with the type of personality. Keywords: Personality, Type job, MBTI.